Itu Pengembangan Modul Berbasis STEM pada Materi Gelombang untuk Peserta Didik Kelas XI SMA - Syoffa Ulya; Fakhruddin; Muhammad Nasir (Postgraduate, University of Mataram, 2023)
The competency standards of class XI graduates in physics learning are deemed inadequate. One element contributing to this is the lack of physics modules based on learning methodologies to guide students' active learning. The goal of this research is to create a STEM-based module on Wave material that is practicable in class XI SMA. Research and development (R&D) utilizing the 4D model (define, design, develop, and disseminate) is employed. Validation sheets and limited trial sheets for students using a four-Likert scale were supplied to experts, teachers, and 30 students from SMA N 8 Mandau. The initial analysis of this research was carried out to determine the student's condition, and documentation was employed as evidence. The data were quantitatively assessed based on the outcomes of expert validation, teachers, and limited student trials. The validation using the average value performed by three expert validators or experts yielded a validation value of 0.81, while the score acquired from three user or teacher validators was 0.93, and the results of the limited trial of students yielded a validation value of 0.80. The results in the form of STEM-based modules on wave material in class XI SMA that match the criteria are high. Based on the results, the STEM-based curriculum is appropriate for use in class XI SMA.